Mangosteen pericarp extract embedded in electrospun PVP nanofiber mats: physicochemical properties and release mechanism of α-mangostin - Sriyanti I (Dove Medical Press, 2018)
Ida Sriyanti,1–3 Dhewa Edikresnha,1,2 Annisa Rahma,4 Muhammad Miftahul Munir,1,2 Heni Rachmawati,4,5 Khairurrijal Khairurrijal1,2 1Department of Physics, Faculty of Mathematics and Natural Sciences, 2Research Center for Bioscience and Biotechnology, Institute for Research and Community Services, Institut Teknologi Bandung, Bandung, 3Department of Physics Education, Faculty of Education, Universitas Sriwijaya, Palembang, 4Pharmaceutics Research Division, School of Pharmacy, 5Research Center for Nanoscience and Nanotechnology, Institute for Research and Community Services, Institut Teknologi Bandung, Bandung, Indonesia Background: α-Mangostin is a major active compound of mangosteen (Garcinia mangostana L.) pericarp extract (MPE) that has potent antioxidant activity. Unfortunately, its poor aqueous solubility limits its therapeutic application. Purpose: This paper reports a promising approach to improve the clinical use of this substance through electrospinning technique. Methods: Polyvinylpyrrolidone (PVP) was explored as a hydrophilic matrix to carry α-mangostin in MPE. Physicochemical properties of MPE:PVP nanofibers with various extract-to-polymer ratios were studied, including morphology, size, crystallinity, chemical interaction, and thermal behavior. Antioxidant activity and the release of α-mangostin, as the chemical marker of MPE, from the resulting fibers were investigated. Results: It was obtained that the MPE:PVP nanofiber mats were flat, bead-free, and in a size range of 387–586 nm. Peak shifts in Fourier-transform infrared spectra of PVP in the presence of MPE suggested hydrogen bond formation between MPE and PVP. The differential scanning calorimetric study revealed a noticeable endothermic event at 119°C in MPE:PVP nanofibers, indicating vaporization of moisture residue. This confirmed hygroscopic property of PVP. The absence of crystalline peaks of MPE at 2θ of 5.99°, 11.62°, and 13.01° in the X-ray diffraction patterns of electrospun MPE:PVP nanofibers showed amorphization of MPE by PVP after being electrospun. The radical scavenging activity of MPE:PVP nanofibers exhibited lower IC50 value (55–67 µg/mL) in comparison with pure MPE (69 µg/mL). The PVP:MPE nanofibers tremendously increased the antioxidant activity of α-mangostin as well as its release rate. Applying high voltage in electrospinning process did not destroy the chemical structure of α-mangostin as indicated by retained in vitro antioxidant activity. The release rate of α-mangostin significantly increased from 35% to over 90% in 60 minutes. The release of α-mangostin from MPE:PVP nanofibers was dependent on α-mangostin concentration and particle size, as confirmed by the first-order kinetic model as well as the Hixson–Crowell kinetic model. Conclusion: We successfully synthesized MPE:PVP nanofiber mats with enhanced antioxidant activity and release rate, which can potentially improve the therapeutic effects offered by MPE. Keywords: α-mangostin, mangosteen, polyvinylpyrrolidone, electrospinning, nanofiber, drug delivery system